Individual interventions, collective lessons: Developing mid-range theory on women’s groups to improve health - Desai, Sapna; Kumar, Neha; Gram, Lu; Hazra, Avishek; Sanyal, Kaliat Ammu; Sivaram, Sharmada (International Society of Global Health, 2024)
Background Interventions with women’s groups have been widely implemented to improve health outcomes in low- and middle-income settings, particularly India. While there is a large evidence base on the effectiveness of single interventions, it is challenging to predict whether a women’s group intervention delivered in one setting can be expected to work in another.